1987
DOI: 10.7164/antibiotics.40.1475
|View full text |Cite
|
Sign up to set email alerts
|

Okilactomycin, a novel antibiotic produced by a Streptomyces species. I. Taxonomy, fermentation, isolation and characterization.

Abstract: Okilactomycin, a novel antibiotic, was isolated from the culture filtrate of a strain of actinomycetes. The producing organism, strain YP-02908L, was identified as Streptomyces griseoflavus subsp. zamamiensis subsp. nov. The antibiotic was extracted with ethyl acetate and purified by silica gel column chromatography. It was obtained as colorless prisms from a dichloromethane solution. It exhibited weak antimicrobial activity against Grampositive organisms in vitro. It also exhibited antitumor activity against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The 13 C NMR spectrum ( 21.2) indicated differences between the two compounds. The proton and carbon chemical shifts of C-17 shifted significantly upfield due to the absence of conjugation.…”
Section: Structure Elucidationmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 C NMR spectrum ( 21.2) indicated differences between the two compounds. The proton and carbon chemical shifts of C-17 shifted significantly upfield due to the absence of conjugation.…”
Section: Structure Elucidationmentioning
confidence: 99%
“…MIC data observed in this study are consistent with that reported earlier. 21 Compound 1 did not show activity against Gram-negative bacteria, but did inhibit growth of the Escherichia coli (envA/tolC) strain, which harbors mutated membrane and efflux pump, and showed an MIC of 64 mg ml À1 . The other four compounds were significantly less active in this assay with only 5 showing a weak activity against S. pneumoniae and also E. coli.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The compound was also described as cytotoxic against some leukemia cell lines with IC 50 ranging from 0.09 to 0.037 mg/mL. 69 Okilactomycin and four congeners okilactomycin A, B, C and D (21)(22)(23)(24) were recently described by our group as produced by a strain of Streptomyces scabrisporus. 70 These compounds were identified from the twoplate antisense RpsD screening where okilactomycin remained the most active compound inhibiting Streptococcus pneumoniae (MIC of 8-16 mg/mL), Enterococcus faecalis (MIC of 16 mg/mL) and Bacillus subtilis (MIC of 4-16 mg/mL).…”
Section: Novel Approaches To Exploit Natural Products From Microbial mentioning
confidence: 99%
“…14 Okilactomycin is a polyketide compound reported to have antitumor and weak antibacterial activity. 15 Recently, Zhang et al 16 confirmed that its mode of action in bacterial cells is via inhibition of RNA synthesis. Piloquinone is a phenanthrenequinone and exhibits antibacterial activity, 17 although the mode of action is not known.…”
mentioning
confidence: 94%